The Digital Sanctuary: Assessing the Efficacy of Mobile Applications for Mindfulness and Stress Reduction in Digital Health - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2025)
The pervasive challenge of chronic stress in modern professional life has fueled a growing demand for accessible and scalable mental wellness solutions. In r...
Keywords: Digital Health; Artificial Intelligence; Healthcare Innovation